Evaluación de la actitud ambiental basada en el comportamiento de los habitantes de la provincia Los Ríos, caso de estudio cantón Quevedo, año 2018 - Vera Cueva, Silvia Lissette. (2018)
The purpose of the study was to evaluate the environmental behavior of the citizens of the province of Los Ríos, 583 surveys were conducted, and as a case study Quevedo canton was evaluated with 383 surveys, as it is the canton with the largest population, Due to its economic development due to the large number of industries and agricultural production, the environmental attitude was represented by seven dimensions with 70 questions according to the Kaiser questionnaire, being: energy conservation, water consumption, mobility and transport, recycling, avoiding waste, consumerism and vicarious behavior towards conservation constituted by items that express a behavior according to their level of dimension. The probabilistic test of the Rasch model was used in the R program with the "Mirt" package of the Item Response Theory (TRI), according to the analysis the items are from easy average to medium, it does not require having a high ability to answer well this questionnaire (0,5 to 2,1) being; V1, V2, V4, V13, V19, V17, V16, V15, V23, V41, V42, V51, V52, V56V61, V162, V63, V64, V66. The inhabitants of the province of Los Ríos indicated to have an environmental attitude was 2.59 ± 0.38 (Disagree) this value differs statistically from the desired value (4; Agree) p = 0.001 and for the study case of the Quevedo canton presents an initial diagnosis of 2.45 ± 0.40 (disagreement) this value differs statistically from the desired value (4; agree) p = 0.001, consequently after the implementation of pro environmental actions through the creation of a manual of good practices The environmental attitudes of the population were improved, a 3.13 ± 0.12 (Indifferent) this value differs statistically from the desired value (4; Agreed) p = 0.001